CLAS S AND HEGEMONY IN KOYOHARU GOTOUGE'S MANGA KIMETSU NO YAIBA: A GRAMSCIAN READING - Mandela, Fitra; Panjaitan, Esterria Romauli; Gitawati, Novi Dwi (Universitas Pakuan, 2024)
Manga as a popular cultural product contains political and ideological content. This qualitative descriptive research will reveal the content of the symbolic content in one of the best-selling manga in the world today entitled Kimetsu No Yaiba by Koyoharu Gotouge. This study reads manga texts with a post-Marxism approach by applying the thought of an Italian Marxist named Antonio Gramsci. He theorized the concept of cultural hegemony, a non-violent social control carried out by the ruling class toward subordinated class that occurs in contemporary capitalist society. Ideological, cultural, and political control have created common sense in society so that people do not realize that their daily lives are always under control. To sharpen the analysis, the study also uses the concept of interpellation by Louis Althusser, another post-Marxist thinker who sees contemporary society believing they are subjects and having control over themselves while in fact living in an illusion created by the ruling class. This study concludes that the charismatic character, Kagaya Ubuyashiki as the supreme leader of Hashira is a symbol of the ruling class that has succeeded in exercising control through the process of cultural hegemonization to transmit the values he fights for. Meanwhile, Hashira, the nine strongest swordsmen of the demon slayer in the manga, is a symbol of a subordinated class who have internalized the political and cultural values of Kagaya Ubuyashiki.